2019
DOI: 10.1039/c8sm02571a
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of red blood cell suspensions under confined 2D flows

Abstract: Microfluidic experiments and numerical simulations show that red blood cell suspensions self-organize into aligned structures under confined 2D flows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 41 publications
1
33
1
Order By: Relevance
“…3 Above 5% Ht, RBCs cannot be discriminated automatically, due to crowding. 7 Hence, the RBC suspensions examined here, have concentrations commonly studied in microfluidic experiments.…”
Section: Rbcs Solution Preparationmentioning
confidence: 99%
“…3 Above 5% Ht, RBCs cannot be discriminated automatically, due to crowding. 7 Hence, the RBC suspensions examined here, have concentrations commonly studied in microfluidic experiments.…”
Section: Rbcs Solution Preparationmentioning
confidence: 99%
“…Recent studies probing RBC deformability have found that individually stiffened RBCs marginate to the vessel walls in mice capillaries [24], as well as in glass micro-channels [25]. Microfluidic experiments found a decrease in self-organization in quasi-2D confined flows with decreasing RBC deformability [26]. In vitro work also found that with increasing populations of rigid RBCs in flow reduces the amount of leukocyte adhesion to P-selectin coated substrates [27] and recently to an inflamed endothelium [28].…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples consisting of a droplet of 30 mL obtained via pinprick are immediately processed: RBCs are extracted by washing the blood sample 3 times with Dulbecco's phosphate buffer saline without calcium and magnesium (Gibco), adjusted with glucose to 295 mOsm and finally resuspended. All details about the experimental method can be found in Iss et al (2019).…”
Section: Microfluidic Experimentsmentioning
confidence: 99%
“…RBCs are shown to form trains in such configurations, and even lines at specific distances from the walls in some cases. Experiments in microfluidic channels demonstrate the existence of such a phenomenon and provide statistics about train formation (Iss et al 2019). Numerical simulations allow dedicated test cases supporting the analysis of the flows, to identify the physical mechanisms at the origin of these specific organizations.…”
Section: Introductionmentioning
confidence: 98%